Antagonistic activity of grape microorganisms against mycotoxigenic fungi - Трегуб, В. І.; Калашник, Я. О.; Осадчий, А. В.; Сас, М. О. (Problems of Environmental Biotechnology, 2017)
The article presents the screening results of habitats of microorganisms with antagonistic properties against mycotoxigenic fungi of the genus Penicillium and Aspergillus. Yeast and bacteria from the surface of grapes of different breed were isolated. Antagonistic properties of isolated microorganisms were evaluated.